Experimental and theoretical insights into the formation of weak hydrogen bonds and H⋯H bonding interactions in the solid-state structure of two eucalyptol derivatives. (4th March 2022) - Galvez, Carolina E.; Piro, Oscar E.; Echeverría, Gustavo A.; Robles, Norma Lis; Lezama, José O. G.; Sankaran, Sankaran Venkatachalam; Thamotharan, Subbiah; Villecco, Margarita B.; Loandos, María del H.; Gil, Diego M.
Abstract : We report the synthesis and X-ray solid-state structure of two eucalyptol derivatives. Both compounds form self-assembled dimers establishing C–H⋯O hydrogen bonds and H⋯H bonding interactions. Abstract : Two eucalyptol derivatives, namely 1, 3, 3-trimethyl-2-oxabicycle[2.2.2]oct-5-yl acetate (4 ) and 1, 3, 3-trimethyl-2-oxabicycle[2.2.2]oct-5, 8-yl acetate (6 ) have been synthesized and characterized. Their crystal structures have been solved by single-crystal X-ray diffraction methods indicating that the molecular conformation of both compounds is stabilized by intramolecular C–H⋯O bonds between the H-atoms of the methyl group from the eucalyptol moiety and the O-atom of the acetoxy group. In addition, we have performed a detailed investigation of the intermolecular interactions that stabilize the crystal packing of both structures by using Hirshfeld surface analysis and their associated two-dimensional fingerprint plots. The analysis reveals that the solid-state structure of compounds 4 and 6 is mainly stabilized by C–H⋯O hydrogen bonds and H⋯H bonding interactions. These interactions have also been described and studied energetically using DFT calculations. The nature and strength of these intermolecular contacts have been rationalized by using several computational tools including molecular electrostatic potential (MEP) surfaces, natural bond orbital analysis (NBO), Bader's theory of atoms in molecules (QTAIM) and non-covalent interaction plot (NCI plot) index methods. Furthermore, the intermolecular contacts observed in the crystal lattice of both compounds were experimentally studied through vibrational (IR and Raman) and 1 H and 13 C NMR spectra. The computational molecular docking analysis of the compounds has been carried out against five potential leishmanial drug targets and the main protease of SARS-CoV-2.